2021
DOI: 10.4236/tel.2021.113039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil Rent on Economic Development in the Republic of Congo

Abstract: The objective of this study is to analyze the effects of oil rent on economic development in Congo over a period from 1987 to 2016. Following the estimation of the Vector Error Correction Model (VECM), the result shows that the dependence on oil rent negatively affects the development of Congo. The poor performance of growth and development in the Congo is mainly linked to the deterioration of governance and the generalization of corruption. This result allows us to formulate an economic policy implication tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The work of Sachs and Warner (1995) further reinforces the negative effect of natural resources on output growth in a panel study of 18 countries over the period 1971-89. In the work of Mbingui et al (2021) which analyzed the nexus of oil rent and economic development in Congo between 1987 and 2016, it was also observed that oil rent depresses economic performance. While affirming the negative effect of oil rent on economic growth, Ramey and Ramey (1995) attribute the negative result to price volatility of natural resources.…”
Section: Oil Rent and Economic Growthmentioning
confidence: 99%
“…The work of Sachs and Warner (1995) further reinforces the negative effect of natural resources on output growth in a panel study of 18 countries over the period 1971-89. In the work of Mbingui et al (2021) which analyzed the nexus of oil rent and economic development in Congo between 1987 and 2016, it was also observed that oil rent depresses economic performance. While affirming the negative effect of oil rent on economic growth, Ramey and Ramey (1995) attribute the negative result to price volatility of natural resources.…”
Section: Oil Rent and Economic Growthmentioning
confidence: 99%
“…According to the study by Mbingui et al (2021), evidence from Error Correction Model (ECM) seems that the country suffers from the 'resource curse' hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%